IMPLEMENTASI KEBIJAKAN KAWASAN RAMAH LANSIA DI KABUPATEN DHARMASRAYA, PROVINSI SUMATERA BARAT - M Iqbal Sarabayan Pazka; Ria Ariany; Desna Aromatica (Jurnal Ilmu Sosial dan Ilmu Politik)
The high number of elderly people, namely 7.01%, is the basis for the Dharmasraya Regency Government to make the elderly one of the regional problems that must be resolved. Based on the guidelines issued by the Central Government through the Ministry of Social Affairs, Dharmasraya Regency issued an Elderly Area Policy through the 2020-2024 Regional Medium Term Development Plan. This research aims to describe and analyze the Implementation of the Elderly Dharmasraya Regency Policy. This research uses Edward III's theory 4 variables to determine the success of implementing a policy: communication, resources, disposition, and bureaucratic structure. The research results show that characteristics within agencies, a clear division of tasks and responsibilities, and good coordination between agencies are key factors for success. Despite the government's commitment to providing adequate funding, there are still potential problems in allocating and using funds that are not on target due to a lack of supervision and monitoring. So, concrete steps need to be taken to improve coordination and ensure that all parties involved have effective communication channels.